From the Paradigm of ‘Listen to the Doctor’, to ‘Listen to the Patient’ - Peter Johannes Manoppo (Jurnal Etika Kedokteran Indonesia, 2020)
Nowadays, the paradigm of ‘Listen to the Doctor’ is weakening in health-care-delivery. The higher expectation of health-care-delivery quality expectation, the better patient-best-preference, and the more complicated system in health-care-delivery, have led to the shift of the paradigm to ‘Listen to the Patient’. Ethically, these situations are enhancing the bargaining position of the patient based on the principle of respect for autonomy. The principles of ethics in health-care- delivery are very important as the proper ground to anticipate the possibilities of unethical behavior by the health-care-provider and caregiver. Those evolutions are also enhancing the efforts of improving the quality of medical human resources, up-to-date medical technology, novel medical researches, and efficient cost-benefit ratio, so that the patient’s health, safety, quality-of-life, and patient-best-preference, can be achieved on the highest level. The paradigm of ‘Listen to the Patient’, which is in line with the principle of respect for autonomy, should be implemented to improve health governance and create the best health-care-delivery quality, good quality-of-life, patient safety, and patient-best-preference to any extent.